Optimizing Tumor-Targeting Drug Delivery of Potent Anti-Cancer Drug Using Doe-Guided Solid Lipid Nanoparticle Formulation: In vitro Cell Line Studies and Histopathological Analysis - Sunitha, Ramineni; Sivadasu, Praveen; Rao, Pathange Bharghava Bhushan; Gunda, Raghavendra Kumar (Indian Journal of Pharmaceutical Education and Research)
Background: Lapatinib Ditosylate emerges as a notable contender; it functions as potent selective dual tyrosine kinases ErbB-2 and EGFR inhibitor and it is a class-II drug. The present work focuses on the development of Lapatanib loaded SLNs for targeting Breast Cancer. Materials and Methods: By employing Box-Behnken design, this study evaluates the impact of three key factors on the formulation of Lapatinib-loaded SLNs: the drug-to-lipid ratio (VX1), the concentration of Labrafil (lipid phase surfactant) (VX2), and the sonication time (VX3). The outcomes of this research will focus on two primary responses: the average particle size (Y1) and the % EE (Y2). The prepared SLNs were studied for percent drug content, PSD, % EE, zetapotential, in vitro drug release studies, Invitro screening of anticancer efficacy by cell line studies and in vivo studies through Histopathological studies. Results: From research findings, the optimal formulation was selected by achieving encapsulation efficiency exceeding 85% and particle sizes under 250 nm; additionally, it was observed that the drug release rate was enhanced at pH 5.0 compared to pH 7.4, while invitro studies demonstrated that LP-SLNs exhibited an IC50 nearly 6 times lower against SKBr3 cells compared to the LS formulation, signifying a markedly superior anticancer efficacy, further supported by histopathological examinations revealing that LP-SLNs significantly mitigated liver toxicity. Conclusion: This comprehensive investigation not only reaffirms the utility of SLNs in improving the delivery and effectiveness of anticancer agents but also accentuates the potential of creating tailored formulations that address the complex challenges inherent in oncological treatments.
Keywords: Lapatanib; SLNs; Box Behnken Design; Cell Line Studies; Histopathological Studies and Screening of Anticancer Efficacy